2021
DOI: 10.1136/bmjopen-2020-046529
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of liver fibrosis and associated risk factors in the Korean general population: a retrospective cross-sectional study

Abstract: ObjectivesThe health burden of chronic liver disease is increasing worldwide. Its main histological consequence is liver fibrosis, and eventually cirrhosis. This process is rarely diagnosed at the pre-cirrhotic stage due to it being asymptomatic. Little is known about the prevalence of liver fibrosis and associated risk factors in the general population. The aims of this study were to determine the prevalence and distribution of liver fibrosis using magnetic resonance elastography (MRE), as well as the risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
1
27
0
1
Order By: Relevance
“…We identified a high prevalence among Hispanic Americans in accordance with Watt et al 46 In addition, more than 20% of patients with diabetes had significant liver fibrosis, which was also observed in other studies. 16,48 Studies have shown that hyperglycemia in patients with diabetes could increase the severity of chronic inflammation 49 and activate the IRS1-PI3K-Akt signaling pathway to stimulate the proliferation of HSCs, whereas activated HSCs promote the overproduction and deposition of extracellular matrix during fibrogenesis. [50][51][52] Thus, early screening of liver fibrosis in aging patients with diabetes should be addressed; if positive, antifibrogenic therapies are essential to prevent further progression to irreversible stages.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a high prevalence among Hispanic Americans in accordance with Watt et al 46 In addition, more than 20% of patients with diabetes had significant liver fibrosis, which was also observed in other studies. 16,48 Studies have shown that hyperglycemia in patients with diabetes could increase the severity of chronic inflammation 49 and activate the IRS1-PI3K-Akt signaling pathway to stimulate the proliferation of HSCs, whereas activated HSCs promote the overproduction and deposition of extracellular matrix during fibrogenesis. [50][51][52] Thus, early screening of liver fibrosis in aging patients with diabetes should be addressed; if positive, antifibrogenic therapies are essential to prevent further progression to irreversible stages.…”
Section: Discussionmentioning
confidence: 99%
“…Transient elastography is an economically attractive alternative to liver biopsy and other noninvasive diagnostic tests of liver cirrhosis 221 . A significant prevalence (22.4%) of liver fibrosis was detected using magnetic resonance elastography among Korean asymptomatic HBsAg‐positive patients 222 …”
Section: Burden Of Chronic Viral Hepatitis In Egyptmentioning
confidence: 99%
“… 14 Notably, in a study with Korean health checkup examinees, the prevalence rate of significant liver fibrosis (estimated using magnetic resonance elastography) was higher in subjects with MetS (15.3%) than in those with fatty liver diagnosed by ultrasonography (11.3%). 15 …”
mentioning
confidence: 99%